Dilemma and Path Optimization Faced by Grassroots Governments under the Perspective of Multi-center Governance - Shen, Jun (International Journal of Social Sciences and Public Administration, 2025)
In recent years, network governance has been a frontier topic in public management research in Western countries. As a new governance model, network governance is an attempt by the government to cooperate with private organizations, non-governmental organizations and citizens in the face of an increasingly complex environment, in order to better provide public services to the public. In particular, with the interdependence, contingency and uncertainty of social, political and economic changes, the governance process is no longer limited to the formal structure of the government. The formulation and implementation of public policies need to be completed through a large number of formal and informal institutions, mechanisms and processes. Therefore, this paper intends to study the difficulties and performance of grassroots government management in my country, as well as the root causes of the difficulties, from the perspective of multi-center governance theory; and in connection with the actual situation, it proposes improvement methods and suggestions from the aspects of positioning the functions of grassroots governments, creating consensus and trust in grassroots government network governance, and cultivating and integrating the network structure of grassroots governance, so as to enhance the practical significance of this model of network governance for my country.